PENGEMBANGAN BUKU AJAR PRAGMATIK EDUKASIONAL TERINTEGRASI KONTEKS INTRALINGUAL DAN BUDAYA PADA MAHASISWA PROGRAM MAGISTER PBSI UNIVERSITAS SANATA DHARMA YOGYAKARTA - Mahu, Odilia Jayanti (Universitas Wijaya Kusuma Surabaya, 2019)
Â The main objectives can be detailed as follows: 1) describe the needs needed by the students of the MPBSI, FKIP, University of Sanata Dharma in terms of learning the Pragmatic Education course. 2) describe the development of Educational Pragmatics textbooks integrated intralingual and cultural context in students of the MPBSI Program, FKIP, University of Sanata Dharma in terms of learning educational pragmatic subjects. This research uses research and development (R&D) methods. The results of the development show that textbooks are suitable for use in the learning process. This can be concluded from the results of expert validation, the assessment of lecturers and the results of field trials to students of the Indonesian Language and Literature Education Study Program, University of Sanata Dharma , Yogyakarta.